THE INFLUENCE OF ORGANIZATIONAL CULTURE ON WORK ACHIEVEMENT EMPLOYEES AT SDIT RAHMANIYAH DEPOK - Rizal Rahmawan; Iwan Darmawansyah (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The aim of this reseaThis study aims to determine the effect of organizational culture on employee work perfomance. Research subjects were employees of SDIT Rahmaniyah Depok , especially teachers and educators. The population in this study amounted to 79 respondens consiting of 69 teaching staff and 10 teaching staff. Data analysis in this study uses SPSS version 24 sofware. The results of this study can be concluded that the organization’s influence is positively and significantly affected on work performance is 20,3 %, while 79,7% is influenced by other factors not included in this study such as work motivation, work discipline , canoensation, work design and job satisfaction. Suggestion from this research is the need for socialization of school organization culture such as vision, mission and philoshopy to employees so that they can be clearly understood and widely accepted. It should be held for all employees to encourage improvements in employee performance and not for certain employees.